View in Cuper's Gardens, Lambeth - Shepherd, G.; Dale (Tufts Archival Research Center, 2008)
Showing the orchestra at the time it was occupied by Messieurs Beaufoys for the British Wine Manufactory. This illustration is from Robert Wilkinson's "Londina Illustrata," vol. 2.